2022
DOI: 10.3390/vaccines10020162
|View full text |Cite
|
Sign up to set email alerts
|

Selection of an Optimal Recombinant Egyptian H9N2 Avian Influenza Vaccine Strain for Poultry with High Antigenicity and Safety

Abstract: For the development of an optimized Egyptian H9N2 vaccine candidate virus for poultry, various recombinant Egyptian H9N2 viruses generated by a PR8-based reverse genetics system were compared in terms of their productivity and biosafety since Egyptian H9N2 avian influenza viruses already possess mammalian pathogenicity-related mutations in the hemagglutinin (HA), neuraminidase (NA), and PB2 genes. The Egyptian HA and NA genes were more compatible with PR8 than with H9N2 AIV (01310) internal genes, and the 0131… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 58 publications
(87 reference statements)
1
4
0
Order By: Relevance
“…The conflicting results may be partially explained by the increased resistance of rSL20(P)-L226Q to non-specific inhibitors in SPF chicken and mouse serum. A similar result was also reported in the G1-lineage Egyptian H9N2 strains (Figure 3) [35]. Serum contains heat-stable α and γ inhibitors, as well as heat-labile β inhibitors.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…The conflicting results may be partially explained by the increased resistance of rSL20(P)-L226Q to non-specific inhibitors in SPF chicken and mouse serum. A similar result was also reported in the G1-lineage Egyptian H9N2 strains (Figure 3) [35]. Serum contains heat-stable α and γ inhibitors, as well as heat-labile β inhibitors.…”
Section: Discussionsupporting
confidence: 88%
“…In a previous study, we observed lower immunogenicity in the G1-lineage Egyptian H9N2 vaccine strain with the L226Q mutation. This was hypothesized to be due to the masking of HA epitopes by formalin-mediated cross-linking of bound sialoproteins [35]. In this study, we did not find an effect of L226Q on immunogenicity, but the HI titer to rSL20(P)-L226Q was significantly lower than that of rSL20(P) (Table 4).…”
Section: Discussionmentioning
confidence: 49%
See 3 more Smart Citations